FAKTOR-FAKTOR PEMILIK BANGUNAN TIDAK MENGURUS IZIN MENDIRIKAN BANGUNAN (IMB) DI KOTA BUKITTINGGI - aini Khalid; ahyuni .; febriandi andi (JURNAL BUANA, 2017)
This study discusses the factors of the building owner does not take care of building permit in Bukittinggi City. The sample in this research is the owner of the building that does not take care of building permit in Bukittinggi City with the population of 285 and the sample is 74 people. This research is conducted by collecting data by observation, interview and questionnaire with delphi method as analysis technique.There are 5 factors that affect the building owner does not take care of building permit in Bukittinggi City that is not know IMB rules, no fees to take care of IMB, old IMB management and procedures difficult, not enough administrative and No time to take care of IMB. The most influential factor felt by the building owner is there is no cost to take care of building permit. Constraints in the management of IMB are 1) The community does not understand the procedures, 2) the lack of public awareness to pay restribusi IMB, 3) The intention of the community to violate the rules that apply from the local government to permit, 4) No cost, 5) cost of expensive IMB processing 6) No timeliness given in handling 7) Still lack of socialization and lack of supervisor in the field so it is still found new buildings do not have permission.